Stimulated-Raman-adiabatic-passage mechanism in a magnonic environment - Wang, Qi; Braecher, T.; Fleischhauer, M.; Hillebrands, B.; Pirro, Philipp (Applied Physics Letters, 2021)
We discuss the realization of a magnonic version of the STImulated-Raman-Adiabatic-Passage (m-STIRAP) mechanism using micromagnetic simulations. We consider the propagation of magnons in curved magnonic directional couplers. Our results demonstrate that quantum-classical analogy phenomena are accessible in magnonics. Specifically, the inherent advantages of the STIRAP mechanism, associated with dark states, can now be utilized in magnonics. Applications of this effect for future magnonic device functionalities and designs are discussed.
CRIS-Team Scopus Importer:2023-03-27